Development of Marketing in the Context of A Tourism Pandemic in Uzbekistan - Ramazonovma, Muhammadova Dilovar (Indonesian Journal of Innovation Studies, 2022)
The article analyzes the basic foundations of marketing in tourism. The author analyzes the methodology of tourism marketing, which is relevant in the current market conditions after the Pandemic. Based on theoretical materials and practical research by leading scientists in this field, as a result of the article, conclusions were drawn regarding the development of tourism in tourism at the informatization of society and globalization of the market in Uzbekistan. The paper formulates specific areas of current research in tourism marketing for the pandemic period. Furthermore, the article discusses the conceptual foundations of marketing in the tourism industry, its features, functions, the need to use modern information technologies.